Compare of Interfractional Setup Reproducibility Between Vacuum-Lock Bag and Thermoplastic Mask in Radiotherapy for Breast Cancer. (September 2021) - Song, Yaqi; Peng, Jin; Chen, Qianfeng; Luo, Honglei
Background: This study aimed to analyze the difference of setup reproducibility between Vacuum-lock bag and Thermoplastic mask in the radiotherapy for breast cancer.Methods: A total of 100 invasive breast carcinoma patients were collected, among whom 50 patients were immobilized with Vacuum-lock bag (VB group), and the other 50 patients were immobilized with Thermoplastic mask (TM group). Set up reproducibility in different axes and comfort levels between two groups at three treatment progress points during the radiation therapy were collected and analyzed.Results: The linear regression model showed that fixed device was an independent factor of radiotherapy setup error (SE). Further subgroup analysis based on different axes showed that the SE caused by the fixed device was obvious in all directions. The comfort level in the VB group was significantly larger than that in the TM group at the beginning of treatment, reduced as the treatment progress going on, and finally disappeared within three weeks.Conclusions: Thermoplastic mask could significantly reduce positioning errors in the radiotherapy of breast cancer. Although more discomfort was found in the TM group, it could be eliminated as the treatment progresses.